Fenomena nafkah pasca perceraian dengan nominal simbolis: analisis kasus rp100 pada perceraian tasya farasya - Romadhona, Aisyah (Maliki Interdisciplinary Journal, 2025)
The phenomenon of celebrity divorce often attracts public attention, not only due to its personal aspects but also because it raises broader legal issues. One notable case is the divorce of Tasya Farasya, in which post-divorce maintenance was set at a symbolic amount of Rp100. This exceptionally small figure has sparked debate, particularly regarding justice, fairness, and its compliance with both Islamic law and Indonesia’s positive law. This article aims to analyze the phenomenon through a normative review of Islamic legal sources, Law No. 1 of 1974 on Marriage, and the Compilation of Islamic Law (KHI). The method applied is a literature study with a normative juridical approach, examining statutory provisions, academic literature, and opinions of Islamic scholars as well as legal experts. The analysis reveals that post-divorce maintenance should be determined based on the principle of fairness, taking into account the husband’s ability and the wife’s needs. The symbolic amount of Rp100 does not reflect substantive justice and is more formal than functional. From an Islamic law perspective, maintenance carries moral responsibility and religious value; thus, an unreasonable nominal may neglect the objectives of sharia (maqashid al-sharia), particularly the protection of women’s rights. In Indonesian positive law, although court rulings are binding, they should still uphold the principles of justice and humanity. Therefore, this case provides a critical reflection on the need for consistency in the application of family law, emphasizing not mere legal formality but the realization of justice and public welfare.